Effects of Bluetooth device electromagnetic field on hearing: pilot study - Balachandran, R.; Prepagaran, N.; Rahmat, O.; Zulkiflee, A.B.; Hufaida, K.S. (Cambridge University Press, 2012)
Background:The Bluetooth wireless headset has been promoted as a 'hands-free' device with a low emission of electromagnetic radiation.Objective:To evaluate potential changes in hearing function as a consequence of using Bluetooth devices, by assessing changes in pure tone audiography and distortion production otoacoustic emissions.Design:Prospective study.Materials and methods:Thirty adult volunteers were exposed to a Bluetooth headset device (1) on 'standby' setting for 6 hours and (2) at full power for 10 minutes. Post-exposure hearing was evaluated using pure tone audiography and distortion production otoacoustic emission testing.Results:There were no statistically significant changes in hearing, as measured above, following either exposure type.Conclusion:Exposure to the electromagnetic field emitted by a Bluetooth headset, as described above, did not decrease hearing thresholds or alter distortion product otoacoustic emissions.